The Relationship Between Death and Religion in Cultural Scripts on Death and Dying Among the Sample of Tehran Residents - Sare Mazinani Shariati; Reza TaslimiTehrani (Taḥqīqāt-i Farhangī-i Īrān)
This article aims at understanding ordinary Tehran residents’ attitudes towards Death and Dying and recognizes the relationship between Death and Religion in their thoughts. Using Grounded Theory as method and semi structured interview as a technique, we reached to nine different Cultural scripts of death and dying among interviewees, including: fatalistic death, resurrection-oriented death, martyrdom-oriented death, mystical death, secular death, aesthetic/nihilistic death, agnostic death, and ambiguity-oriented death. Furthermore, we recognized religious and non-religious cultural scripts besides the rationalization and individualization of religion among them. According to our findings, there is no accordance between some interviewees’ thoughts and beliefs with their behavior and lifestyle so that one cannot guess people’s attitudes towards death and dying from their behavior or their appearance. In other words, we face no structural Homology between their ideas and their lifestyle. Moreover, most interviewees had mixed ideas and beliefs about death and dying, and it can indicate the social and cultural complexity of Tehran society.